EQUVALENCE PRINCIPLE IMPLIES A GRAVITATIONAL-REDSHIFT PROPORTIONAL SPACE DILATION AND HENCE GLOBAL CONSTANCY OF c - Rossler, Otto E. (European Scientific Journal, ESJ, 2014)
The equivalence principle, Einsteinâ€™s famous 1907 paradigm of the constantly accelerating extended long rocketship in outer space, has a new implication. The constant recession speed of the bottom relative to the tip causes not only a â€œgravitational time dilationâ€ (redshift) whereby the distance paradoxically remains invariant; it in addition also causes a proportional blowup of size valid downstairs â€“ â€œgravitational space dilation.â€ This result implies a return to the global constancy of the speed of light c of special relativity in the equivalence principle and therefore in gravitation. The consequences are staggering (no global space expansion, no gravitational waves, no Hawking evaporation, no incompatibility between gravitation and quantum mechanics). A global-c transform of the Einstein equation is preprogrammed.